Integrating Local Cultural Animated Video as a Media in English Language Teaching to Promote Students’ Character in Gorontalo Elementary Schools - Indah Wardaty Saud; Yurni Rahman (Universitas PGRI Semarang, 2019)
Attractive media for English as a foreign language at the elementary school needs to be elaborated with the cultural values. The aim is for students to have a fun and authentic learning experience because the media contains culture that they often see and even engage in. At the end, learning media integrated with local cultural values when applied to English learning in elementary schools can support the process of promoting students' characters. This study aims to find an animated video design with local cultural values in English language learning to promote the character of elementary school students in Gorontalo. It focuses on exploring students and English teachers perception towards integrating local cultural animated video in English language teaching media to promote students’ character. This study uses Research and Development design in the form of need analysis with mixed method data analysis. The respondents involve are 250 students in fifteen elementary schools in Gorontalo. The researcher uses questionnaire and interview to collect the data. The result shows that the students agreed that integrating animated video in English language teaching and learning are an interesting idea. They preferred choosing traditional games and songs as topics to be learnt with English. Meanwhile, the English teachers believed that the implementation of media or learning resources with Gorontalo cultural values can promote the character of elementary school students. However, teachers were unfamiliar with cultural integration in learning English. They have never found a media or source of learning English that covers Gorontalo culture. The culture that is considered necessary to be integrated together with English learning is Gorontalo tourism spots, and traditional dances and games.